El comercio en México y su encuentro con la globalización. El caso Sonora - Vázquez Ruiz, Miguel Ángel (Frontera Norte, 2017)
Carmen O. Bocanegra Gastélum, Hermosillo, Sonora, Universidad de Sonora, 2008, 393 pp.